Pelaksanaan Strategi Komunikasi Persuasi Coffeshop Delapan Meter - Muhammad Ulil Albab; Imanuel Deny Krisna Aji (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Eight Meter Coffee Shop, located in the Mojokerto area, has become a popular gathering spot, especially for the people of Mojokerto City. According to its Google Business page, Eight Meter Coffee Shop has gained popularity with a rating of 4.6 out of around 295 recorded reviews. The shop offers an industrial concept and a view of the rice fields, enhancing the experience for visitors. Apart from its well-crafted ambiance, Eight Meter Coffee Shop employs various communication strategies to engage its customers effectively. In this study, the persuasive communication tactics employed by Eight Meter Coffee Shop are analyzed using a quasi-qualitative research methodology, involving data collection, analysis, conclusion drawing, and application of findings in a broader context. Informants involved in this research include the baristas, the owner, and patrons within the Coffee Shop. Additionally, a quasi-qualitative research design is utilized to analyze data at various levels, classify it for easier utilization, and compile it into a scholarly report. The research findings highlight the importance of considering appropriate design in advertising Eight Meter Coffee Shop, focusing on product quality with added attractive elements, and seizing specific moments to capture the attention of new audiences. Moreover, strengthening ties with the local community and involving them in promotional activities can be effective strategies for increasing foot traffic and customer engagement.